2013
DOI: 10.1103/physreva.88.062304
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent linear-optical qubit amplifier

Abstract: We propose a linear-optical setup for heralded qubit amplification with tunable output qubit fidelity. We study its success probability as a function of output qubit fidelity showing that at the expense of lower fidelity, the setup can considerably increase probability of successful operation. These results are subsequently applied in a proposal for state dependent qubit amplification. Similarly to state-dependent quantum cloning, the a priori information about the input state allows to optimize the qubit ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…It was shown that the success probability didn't decrease asymptotically to zero even with the increasing gain. Bartkiewicz et al studied the statedependent qubit amplification with success probability as a function of output qubit fidelity [26]. The qubit amplification procedure could be optimized to obtain better fidelity versus success probability.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the success probability didn't decrease asymptotically to zero even with the increasing gain. Bartkiewicz et al studied the statedependent qubit amplification with success probability as a function of output qubit fidelity [26]. The qubit amplification procedure could be optimized to obtain better fidelity versus success probability.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the originall proposal, perfect gain could have been reached only asymptotically, however this shortcomming has been removed by Pitkanen et al [7]. Recently, it has been shown that, if a heralded amplifier is allowed to introduce some noise, its gain and herading rate be increased [10] which also depends on the set of qubits to be amplified.…”
Section: Introductionmentioning
confidence: 99%
“…The heralded amplifier and its improvments (see, eg., Ref. [7]) or alternarive schemes using entanglement [8][9][10] have been demonstrated to be useful especially in the * bark@amu.edu.pl context of quantum key distribution. Interesingly the improved qubit amplifier described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Single-photon amplification is a promising method to overcome the photon loss problem by amplifying the probability of non-vacuum state, 13) which can be achieved by using single-photon or entangled photon pairs as auxiliary. [14][15][16][17][18][19][20][21][22][23] Xiang et al experimentally demonstrated a nondeterministic single-photon-assisted noiseless linear amplifier and used it to entanglement distillation. 14) This scheme was heralded, and could create a freely-propagating amplified state forming the basis of practical quantum communication.…”
mentioning
confidence: 99%
“…19) They achieved infinite gain with the success probability equal to that of standard teleportation, and presented its applications in entanglement distillation and quantum key distribution. Bartkiewicz et al presented a statedependent qubit amplification based on entanglement, 20) and its probability could be seen as a function of output fidelity. It was a trade-off between better fidelity and success probability to optimize the qubit amplification.…”
mentioning
confidence: 99%